2016
DOI: 10.1039/c5gc02816g
|View full text |Cite
|
Sign up to set email alerts
|

Imposed hydrophobic interactions by NaCl: accountable attribute for the synthesis of spiro[acenaphthylene-1,5′-pyrrolo[1,2-c]thiazole] derivatives via 1,3-dipolar cycloaddition reaction in aqueous medium

Abstract: The significance of hydrophobicity for the synthesis of spiro[acenaphthylene-1,5′-pyrrolo[1,2-c]thiazole] derivatives by a 1,3-dipolar cycloaddition reaction in aqueous medium is outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 89 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…These kosmotropes capture the hydrophobic reactant molecules inside the cavity and thus decrease the interaction of reactant molecules. 4345 Therefore, the reaction cannot be carried out in water alone. Compounds like NaCl act as a “salting-out” agent, which increases the hydrophobic effect and thus disturbs the kosmotropes by increasing the cavity formation energy cost in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…These kosmotropes capture the hydrophobic reactant molecules inside the cavity and thus decrease the interaction of reactant molecules. 4345 Therefore, the reaction cannot be carried out in water alone. Compounds like NaCl act as a “salting-out” agent, which increases the hydrophobic effect and thus disturbs the kosmotropes by increasing the cavity formation energy cost in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…The reactions with heteroaromatic aldehydes (entries 20,22) finished in a short time. As the n-pyridinecarboxyaldehydes (n = 3 or 4, entries 20, 21) are rather reactive electrophiles and are completely miscible in water, the reactions with these substrates were incredibly fast (in seconds).…”
Section: Resultsmentioning
confidence: 99%
“…In the earliest works, the amines used to catalyze the reactions presented a considerable level of toxicity. 16,17 Thus, many papers have been published in recent years concerning proposals for ecofriendly reaction conditions, [18][19][20][21][22] in accordance with the principles of green chemistry. [22][23][24][25] From this perspective, many researchers have developed new catalysts involving the mentioned principles.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in extension of our work and in view of this, we demonstrate the metal‐free oxidative coupling of unreactive reactant partner methylarenes and anilines for the formation of amide bonds using GO nanosheets in the presence of TBHP as a co‐oxidant under aqueous medium at room temperature (Scheme ). We have found that the carboxylic acid functional groups on GO nanosheets play a vital role in this metal‐free strategy.…”
Section: Introductionmentioning
confidence: 99%